Study of Silver nano Particales for Anticancer Activity K - Sreedevi; Dr. P. Shivakrishna (International Journal of Medical Toxicology and Legal Medicine, 2024)
Cancer is a leading causeof death world wide,Accounting for nearly 10 million deaths in 2020,According to world health organization.(WHO).About 50 million people worldwide living with cancer. Silvernanoparticles have gained significant attention in recent years for their potent role in cancer prevention and treatment. They contribute to cancer prevention by apoptosis induction,antiproliferative effectsand angiogenic effects. By using green synthesis methods we can synthesize silver nano particales from bacteria ,fungi, plants and animals. In our present study we are synthesizing silver nanoparticles from bacteria through green synthesis and studying for their anti canceractivity. Samples are collected from oil contaminated soils near oil industry in Kamareddy district. Sample are used to isolate bacteria. Isolated bacteria were grown in high amount and centrifuged at 10,000 rpm to get the bacteria.100 ml of supernatant containing bacteria is mixed with 1 ml of silver nitrate and incubated at 30c for 24 hours. After 24 hours yellow colored solution turned into brown indicating formation of silver nano particales Anticancer activity of silver nano particales was evalued by using the MTT assay.formazan crystals formed were dissolved in DMSO, and absorbance was measured at 570 nm using spec photometer the biologically synthesized silver particales were observed at 430 nm.Anticancer activity of AgNp-SD against AS49 , MCF-7, HT29 and CHO-KI Cell lineswere measured.The study evaluated the biocompatibility and cytotoxic effects of biosynthesized silver nanoparticles (AgNPs) compared to cisplatin across four cell lines.